FRI0535 Hand Bone Loss in Early Rheumatoid Arthritis Is Independent of Adalimumab Treatment. A Substudy of The Optimized Treatment Algorithm in Early RA (Opera) Trial. (15th July 2016) - Ørnbjerg, L.M.; Østergaard, M.; Jensen, T.; Hørslev-Petersen, K.; Stengaard-Pedersen, K.; Junker, P.; Ellingsen, T.; Ahlquist, P.; Lindegaard, H.; Linauskas, A.; Schlemmer, A.; Dam, M.Y.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is characterised by progressive destruction of joint bone and loss of periarticular bone mineral. Hand bone loss (HBL) measured by Digital X-ray Radiogrammetry (DXR) has been proposed as a sensitive outcome measure for treatment effect and as a potential predictor of subsequent radiographic progression in RA patients. Objectives: To investigate the effect of adding adalimumab to a methotrexate and intra-articular triamcinolone treat-to-target strategy on one-year HBL (HBLone-year ) in early RA and to determine if HBL6months is associated with radiographic progression after two years. Methods: In a clinical trial (OPERA) of 180 treatment-naive early RA patients (1), bone mineral density (BMD) was estimated from hand radiographs with Digital X-ray radiogrammetry (DXR) at baseline, after 6 months (n=90) and 12 months (n=70) of follow-up. Baseline and two-year radiographs were scored according to the Sharp/van der Heijde method. Baseline characteristics and HBL6months (0–6 months changes in DXR-BMD) were investigated as predictors of structural damage by univariate linear (ΔTotal Sharp/van der Heijde Score (TSS) as dependent variable) and logistic (+/− radiographic progression (ΔTSS>0) as dependent variable) regression analyses. Variables with p<0.10 were included in multivariable models. Results: In 70 patients with available HBLone-year data, HBLone-year was median (InterQuartileRange (IQR)) -1.9 (-3.3; -0.26 mg/cm 2 ) in the placebo-group and -1.8 (-3.6; 0.06) mg/cm 2 in the adalimumab-group, p=0.98, Mann Whitney. Increased HBL (compared to general population reference values (2)) was found in 26/37 and 23/33 patients in the placebo- and adalimumab-groups, Chi-sq=0.99. In 90 patients with HBL6months data and two-year radiographic data, HBL6months was independently associated with ΔTSS after two years (β=-0.086 (95% Confidence Interval= -0.15; -0.025) TSS unit/mg/cm 2 increase, p=0.006), and borderline associated with presence of radiographic progression (ΔTSS>0) (OR 0.96 (0.92–1.0), p=0.10). Conclusions: In early RA, adding adalimumab to a methotrexate-based treat-to-target strategy had no impact on HBLone-year, which was increased in both treatment groups. HBL6months was independently associated with ΔTSS after two years. References: Hørslev-Petersen et al. Ann Rheum Dis. 2015 doi: 10.1136/annrheumdis-2015-208166. Ørnbjerg LM et al. [abstract]. Arthritis Rheumatol. 2015; 67 (suppl 10). Disclosure of Interest: L. Ørnbjerg: None declared, M. Østergaard Grant/research support from: Abbvie, BMS, Boehringer-Ingelheim, Eli Lilly, Janssen, Merck, Pfizer, Roche, UCB, Celgene, Sanofi, Regeneron, Novartis, T. Jensen: None declared, K. Hørslev-Petersen Grant/research support from: Abbvie, Meda, Roche, K. Stengaard-Pedersen Grant/research support from: Meda, Abbvie, Roche, Speakers bureau: UCB, Pfizer, P. Junker: None declared, T. Ellingsen: None declared, P. Ahlquist: None declared, H. Lindegaard Grant/research support from: Boehringer Ingelheim, A. Linauskas: None declared, A. Schlemmer Grant/research support from: Abbvie, Roche, MSD, M. Dam: None declared, I. Hansen: None declared, T. Lottenburger: None declared, C. Ammitzbøll: None declared, A. Jørgensen: None declared, S. Krintel: None declared, J. Raun: None declared, M. Hetland: None declared